Is it possible to complete professional physical education without studying the theory of physical culture? - Сутула [Vasilij Sutula] Василь Опанасович (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Noted the importance of physical education in the Ukrainian society. It was stated that in the curriculum of universities physical culture at this time does not provide the subject «Theory of physical culture». It is shown that for its introduction there are objective conditions. It is concluded that modern professional education must form a world of future professionals of this sphere of public life, which should be not only qualified, but also physically cultural personalities. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>